Hedging with synthetical forwards and the export decision - Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
The paper focusses on currency options as financial hedging instrumenta. Since currency forwards imply the well-known Separation result, it follows for arbitragefree hedging markets that Separation must also hold in option markets if the traded options allow for con-structing a synthetical forward contract. Furthermore export revenue is fully hedged by synthetical forwards, if the risk premium in the put price is equal to the risk premium in the call price.
Keywords: 330